Galen and Pharmaceutical Technology - K. S. Guzev (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2016)
Using certain examples we have shown, that Galen took the properties of the used components and their components into consideration, offered sensible ingredients combinations and blends, and prepared a dosage form, capable of implementing its pharmacological action. The analysis of the materials gave grounds to consider Galen not only as an outstanding doctor, but one of the first manufacturing chemist.